HUBUNGAN PENGETAHUAN DAN SIKAP PEDAGANG JAJANAN ANAK SEKOLAH TERHADAP PENGGUNAAN FORMALIN DAN BORAKS DI SD NEGERI WILAYAH PEDURUNGAN KOTA SEMARANG - Luthfiyah Nur Safitri; Dyah Nur Subandriani; Astidio Noviardhi; Arintina Rahayuni; Ana Yuliah Rahmawati (Poltekkes Kemenkes Semarang, 2019)
Background : Chemical material such as formalin and borax should notfound in food because it can cause nausea, stomachache, vomiting, bloody defecation.But with reason to reduce production costs, take profits and extend the shelf life, many producers who still use these materials.This is due to lack of knowledge and the attitude of the producer indifferent to food security.Objective : Knowing the relationship between knowledge and attitudes of schoolboy snack vendors to the use of formaldehyde and borax in children's snacks in public elementary schools in the urban area of pedurungan Semarang city.Method :This research is a descriptive analytic study with cross sectional design, a total sample of 20 samples of schoolchildren's street vendors. In this study the measuring instruments used were questionnaires and interviews. The test used is Fisher's exact.Results : Trader's knowledge is mostly good (80%)and the attitude of traders mostly supports (60%). The bivariate test results obtained p value 0.05 so there is no relationship between knowledge and attitudes of street food traders to the use of formalin and borax.Conclusion : The use of formalin and borax is not caused by the knowledge and attitudes of traders related to food security.